Entropy optimization of stagnant blood flow systems with tetra-hybrid nano additives under viscous dissipation, joule heating and thermal radiation effects - Meena Rajeswari P; Poulomi De (Case Studies in Thermal Engineering)
Entropy generation optimization has significant applications in biomedical engineering, including angioplasty therapy, more rapid focused medication delivery and streamlining of medical instruments functionality. This study seeks to explore entropy generation optimization in stagnant blood flow region with tetra-hybrid nanofluid through a curved stretching surface embedded by blood tissues. Aiming to enhance heat transfer rate, SiO2+TiO2+Fe2O3+Au nanoparticles are considered with a combination of radiation effects, viscous dissipation and joule heating. Numerical solutions are obtained by Runge-Kutta-Fehlberg 5th order method with shooting strategy. Validation of code is done by comparing the current result of distinct curvature parameter values for drag force to existing studies and attaining high concordance. Numerical results in surface drag force and thermal transmission rate for unsteadiness parameter and curvature parameter are investigated. Improvement of curvature parameter enriches the blood flow's velocity and reduces the pressure distribution. Tetra-hybrid nanofluid volume fraction and platelet shape factor for nanoparticles have efficient heat transfer rate. Curvature parameter enhances the heat transfer rate by 141.4 % and minimizes the resistance of blood flow as 42.49 %. Entropy generation optimization worked well for tetra-hybrid nanofluid compared to pure blood flow, enhanced by 47.7 %. Overall results have major utilization in biomedical engineering field and medical devices optimization.